PERAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN PADA USAHA KING LAUNDRY DI SUMENEP - Nurcholisa , Tila; Wibisono, Aryo (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
In the era of globalization, business competition in Indonesia is now growing very rapidly, especially in the service sector. Especially laundry services, laundry services are a form of service that is growing rapidly in this era. As the King of the Laundry Business in the heart of the city. This research aims to determine the effect of service quality on consumer loyalty which is mediated by consumer satisfaction. The population of this research is King Laundry consumers in Sumenep Regency. The sample consisted of 75 respondents. The data analysis method used is Smart PLS with the PLS-SEM method. The research results show that the results of service quality have a positive and significant effect on consumer loyalty in the King Laundry business. Furthermore, service quality has a positive and significant effect on consumer loyalty through consumer satisfaction at the Sumenep King Laundry business.